2014
DOI: 10.1371/journal.pone.0101530
|View full text |Cite|
|
Sign up to set email alerts
|

miR-146a Ameliorates Liver Ischemia/Reperfusion Injury by Suppressing IRAK1 and TRAF6

Abstract: A critical role of the Toll-like receptor(TLR) and its downstream molecules, including IL-1 receptor-associated kinase 1(IRAK1) and tumor necrosis factor receptor– associated factor 6(TRAF6), in the pathogenesis of liver ischemia/reperfusion (I/R) injury has been documented. Recently a microRNA, miR-146a, was identified as a potent negative regulator of the TLR signaling pathway. In this study, we investigated the role of miR-146a to attenuate TLR signaling and liver I/R injury in vivo and in vitro. miR-146a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 44 publications
(55 reference statements)
2
62
0
Order By: Relevance
“…Some studies show that miR-125a-5p prompted the activation and proliferation of hepatic stellate cell by partially down-regulating FIH1 in liver fibrosis [15], and miR-133a-5p was protective against hypoxia/reoxygenation (H/R) injury in vitro by targeting MAPK6 in hepatocytes [56]. Moreover, miR-146a could ameliorate liver hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6 [12] and miR-494 was protective against hypoxia-induced apoptosis in liver through HIF-1α upregulation by activating PI3K/ Akt pathway [14]. In addition, there is accumulating evidence suggesting that many other miRNAs are involved in liver reactions to hypoxic stress, such as miR-150 downregulation under hypoxia by targeting VEGF-A and HIF1α during liver regeneration [16, 57], miR-192-5p upregulation in hepatocyte injury [13] and increased miR-462/731 cluster in the hypoxia-exposed liver of Megalobrama amblycephala [58] and zebrafish [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show that miR-125a-5p prompted the activation and proliferation of hepatic stellate cell by partially down-regulating FIH1 in liver fibrosis [15], and miR-133a-5p was protective against hypoxia/reoxygenation (H/R) injury in vitro by targeting MAPK6 in hepatocytes [56]. Moreover, miR-146a could ameliorate liver hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6 [12] and miR-494 was protective against hypoxia-induced apoptosis in liver through HIF-1α upregulation by activating PI3K/ Akt pathway [14]. In addition, there is accumulating evidence suggesting that many other miRNAs are involved in liver reactions to hypoxic stress, such as miR-150 downregulation under hypoxia by targeting VEGF-A and HIF1α during liver regeneration [16, 57], miR-192-5p upregulation in hepatocyte injury [13] and increased miR-462/731 cluster in the hypoxia-exposed liver of Megalobrama amblycephala [58] and zebrafish [59].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that miR-182 is also downregulated after hypoxia-ischemia brain injury in neonatal rats [65]. Jiang et al reported that miR-146a-5p could ameliorate ischemia/reperfusion injury in vivo and hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6 in liver [12]. Therefore, it is likely that hypoxia injures the hepatocytes through, at least partially, an inhibitory negative regulation of these two miRNAs, while DOR signaling is able to reverse such negative regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoxia/reoxygenation (H/R) model was created as previous described [20]. Hypoxia preconditioning was performed by culturing cells in a tri-gas incubator with a 1% oxygen concentration according to the manufacturer's instructions.…”
Section: Hypoxia/reoxygenation Modelmentioning
confidence: 99%
“…Moreover, there is evidence that miR-146a may also target other prometastatic genes in breast cancer, including TNF receptor-associated factor 6 (TRAF6), interleukin-1 receptor-associated kinase (IRAK1), epidermal growth factor receptor (EGFR) and metastasis-associated protein 2 (MTA2) (Bhaumik et al, 2008;Hurst et al, 2009;Li et al, 2010;Hung et al, 2013;Ali et al, 2014;Jiang et al, 2014). According to the newly proposed competing endogenous RNA (ceRNA) hypothesis, specific RNAs targeted by the same groups of miRNAs can regulate one another by competitively binding with microRNAs.…”
Section: Introductionmentioning
confidence: 99%